Determinants of rural households' willingness to pay for improved potable water supply in Central Rift Valley Ethiopia: contingent valuation method approach - Shimeles Getinet; Abule Mehare; Aemro Tazeze (Cogent Economics & Finance, 2024)
Access to improved water is a global issue aligned with sustainable economic development. Ethiopia plans to enhance access to safe water through low-cost tech and community mobilization. However, finance is crucial for rural water construction and rehab, and the price mechanisms through users' contributions can improve the cost recovery of rural water supply. Hence, the objective of this study is to investigate rural households' willingness to pay (WTP) for improved potable water supply using the contingent valuation method (CVM). Data collected from a randomly selected 272 sample households were analyzed using descriptive and econometrics analysis. The seemingly unrelated bivariate probit (SUBP) econometric model was used to calculate the mean WTP and identify the determinant factors. The results show that 70.96% of the households were willing to pay the initial bid. The results show that sex, annual farm income, off-farm income, the average time it takes to fetch water, use of water treatment and monthly water expense have a positive and significant effect. Yet, household size, perceptions of the quality and reliability of the existing water supply, and bid values have a negative and significant effect. The mean value for improved potable water supply was 1.80 ETB per 20 liters of Jerrican1. Rural households in the study area are willing to contribute up to 7.4% of their annual income. To ensure the financial sustainability and cost recovery of rural water supply, it may therefore be possible to intervene and adopt a new water price system. The objective of this study was to estimate rural households' willingness to pay improved potable water supply using contingent valuation method. The study reveals the critical need for improved water supply in rural areas, highlighting the significant demand for safe and reliable water supply. It emphasizes the importance of community involvement in water management and provides a platform for collaborative solutions to address water supply challenges. This research provides valuable insights into the willingness of rural households to invest in improved potable water supply, indicating the potential for cost-recovery initiatives and community-driven solutions. The outcome of this study provides relevant information for making sound and well-informed decisions and is essential for developing an optimal pricing strategy which helps to ensure financial sustainability of the rural water supply. It can serve as a baseline data to undertake an appropriate cost-benefit analysis and provide empirical evidence for further researcher on related topics.
Keywords: 330; Contingent valuation; Ethiopia; seeminglyunrelated bivariate probit; water supply; willingnessto pay